(untitled) (Research, Society and Development, 2021)
This article brings some reflections about education and culture, taking as a parameter Freire’s critical perspective. The reflections that we present revolve around the coherence between what is said and what is done (Praxis). Our goal is to: analyze the Freire’s Education categories; Awareness; Culture and Popular Culture crossed by the concept of Praxis, perceiving thinking and acting as inseparable practices for the educators of our time. The methodology utilized is bibliographic review with emphasis on qualitative based narrative review. Therefore, we start from the principle that education is a political act, but also that every critical political act needs to reflect on concrete reality, since it is not given explicitly. It needs to be unveiled. Texts like the one we have here aim to stimulate the awareness process, since this only takes place in praxis. The theme that we present is current and necessary, connecting times that sometimes seem remote, but that in the current situation are pertinent. The results show that the revisiting the works of Paulo Freire is more and more current and is possible to be implemented in the daily life of the educator, we also defend that Freire when developing the concept of Praxis contributes strongly to elucidate the gap between thinking and acting and thus recognize our condition of oppressor / oppressed so that at some point we can overcome it.